IMPACT OF THIAMETHOXAM ON PROTEASES AM ON PROTEASES, AMINASES AND GLUTAMATE DEHYDROGENASE IN SOME TISSUES OF TE DEHYDROGENASE IN SOME TISSUES OF FRESHWATER FISH, CHANNA PUNCTATUS (BLOCH) (BLOCH) - V. ANIL KUMAR; C. JANAIAH; P. VENKATESHWARLU (The Bioscan, 2010)
Sublethal concentration of Thiamethoxam (Organochloride) on the tissues (liver, brain, gill, muscle and kidney) enzyme parameters of teleost fish, Channa punctatus (Bloch) were analysed after 24, 48, 72 and 96 hrs of exposure. The increased neutral and alkaline proteases activities in the different tissues of C. punctatus indicate the damage caused due to impairment of energy supply and alkaline proteases activity indicates higher protein degradation. Therefore, the proteins are denatured leading to more activation of proteases. The activities of asparatate amino transferase (AAT) and alanine amino transferase (ALAT) were enhanced during the toxic exposure of thiamethoxam resulting in incorporation of amino acids into TCA cycle for energy production. The glutamate dehydrogenase (GDH) activity also enhanced levels of amino acids, transminases which might suggest the utilization of proteins under stress conditions of the fish.